Physical Simulation Test for Developing Composite Materials of Non-Hydrophilic Aquifuge in Water-Preserved Mining - Ma, Liqiang; Sun, Hai; Wang, Hui; Wang, Fei; Zhang, Jixiong; Jin, Zhiyuan (Asian Journal of Chemistry, 2014)
With the fluid-solid coupling similar principle, composite materials of aquifuge are developed by physical simulation test for fluid-solid coupling in water-preserved mining and a rational proportion of non-hydrophilic is studied. Sand and gypsum are adopted as the aggregate of physical simulation materials, while vaseline and silicone oil are served as cementing agent. Firstly, water-physical properties of the material, including water absorption, permeability, distensibility and fluid-solid coupling softening effect, have been studied. Then, basic mechanical property of the material, plasticity has been tested on this basis. Finally, a series of rational proportions fit for aquifuge materials have been discovered, i.e., the weight ratios of sand and gypsum is between 5:1 and 7:1, aggregate and cementing agent between 6:1 and 8:1 and vaseline and silicone oil between 1:1 and 3:1. The research results not only can provide a basis for the research of water-preserved mining by physical simulation test, but also can be used for other engineering projects in need of non-hydrophilic composite materials with good plasticity.